Analysis of accountability and service quality of the national zakat amil agency on muzaki trust - Hasrun, Andi; Rokhimah, Rokhimah; Karfin, Karfin; Abdullah Lawang, Karimuddin (Institute of Computer Science (IOCS), 2023)
This research aims to determine the partial and simultaneous influence of accountability and service quality on muzaki's trust in BAZNAS Sorong Regency. The data collection tool used questionnaires which were distributed to 72 respondents and 61 questionnaires were returned which were selected using non-probability sampling techniques. To answer research problems and test hypotheses, the Statistical Program for Social Science (SPSS) V.28 analysis technique was used. The results of this research show that partially accountability has no significant effect on muzaki's trust with a tcount value of 0.227 < ttable 2.001 and a significance value of 0.821 > 0.05, while service quality has a significant effect on muzaki trust in BAZNAS Sorong Regency with a tcount of 3.409 > ttable 2.001 and a significance value 0.001 < 0.05. Furthermore, accountability and service quality simultaneously influence the trust of muzaki in BAZNAS Sorong Regency with a Fcount value of 7.316 > Ftable 2.764 and a significance value of 0.001 < 0.05. Then the contribution of the muzaki trust variable is explained by the accountability and service quality variables with an R-Square value of 20.2%, while the remaining 79.8% is explained by other variables outside this research. Because the contribution of the independent variable has a low percentage, future researchers are expected to be able to increase the number of samples and the number of other independent variables that have an influence on muzaki beliefs, for example knowledge, religiosity, community culture.